The Effect of Arbuscular Mycorrhizae and Sp-36 Fertilizer Application on The Growth of Butternut Squash (Cucurbita Moschata Durch) in Swampy Land - Nita Aprillia; Dewi Erika Adriani; Raihani Wahdah (Postgraduate Program - Lambung Mangkurat University (ULM Press Academic), 2022)
This study aimed to: (1) determine the effect of various doses of arbuscular mycorrhizae with SP-36 fertilizer on the growth of butternut squash in the swampy land; (2) determine the best combination of various doses of arbuscular mycorrhizae with SP-36 fertilizer on the growth and of butternut squash in the swampy land. The research was carried out in the Green House of SMK PP Negeri Banjarbaru from October 2020 to November 2021. The study used a factorial completely randomized design (CRD) with 2 factors. The fist factor was arbuscular mycorrhizae dose (M) which consisted of 4 levels, namely: m0 = Control ; m1 = 5 g tan - 1 equivalent to 0.1 ton ha - 1;m2 = 10 g tan - 1 equivalent to 0.2 ton ha - 1; m3 = 15 g tan - 1 equivalent to 0.3 ton ha - 1.The second factor was SP-36 fertilizer dose (S) fertilizer which consists of 4 levels, namely: s0 = Control; s1 = 1,39 g tan - 1 equivalent to 0,125 ton ha - 1; s2 = 2,22 g tan - 1 equivalent to 0,2 ton ha - ; s3 = 3.06 g tan - 1 equivalent to 0.275 ton ha- 1, combination repeated 3 (three) times, with 6 polybags of them, so that there were 288 plants in total. The result showed that there was an interaction effect on the volume of roots at 2 and 4 weeks after planting, shoot dry weight, root dry weight and shoot root ratio. The single factor of application of arbuscular mycorrhizae and SP-36 fertilizer each had a very significant effect on root colonization. Combination of arbuscular mycorrhizae at a dose of 10 g ton - 1 equivalent to 0.2 ton ha- 1 and SP-36 fertilizer at a dose of 3.06 g ton - 1 equivalent to 0.275 ton ha – 1 could increase the growth of butternut squash in the swampy land.